God, freedom, and human dignity embracing a God-centered identity in a me-centered culture - Highfield, Ron, 1951- (Downers Grove, IL : IVP Academic, 2013)
Ron Highfield traces out the development of Western thought that has led us our current frame of mind from Plato, Augustine and Descartes through Locke, Kant, Blake Bentham, Hegel, Nietzsche--all the way down to Charles Taylor's landmark work Sources of the Self. At the heart of the issue is the modern notion of the autonomous self and the inevitable crisis it provokes for a view of human identity, freedom and dignity found in God. Highfield makes pertinent use of trinitarian theology to show how genuine Christian faith responds to this challenge by directing us to a God who is not in competition with his human creations, but rather who provides us with what we seek but could never give ourselves. --from publisher description
Part 1: The me-centered self. How the me-centered world was born -- Defiance : the Promethean dimension of the modern self -- Subservience : the religion of idols, hypocrites and hirelings -- Indifference : a study in thoughtlessness -- The God of the modern self -- The secret aspirations of the modern self -- Some unwelcome limits on freedom and dignity -- Part 2: The God-centered self. The self-giving God of the Gospel -- The irony of divine "weakness" -- The awakening presence -- A new way of being human being -- The divine adoption -- The emergence of God-centered identity -- The freedom of the children of God -- God's love as the ground and measure of human dignity -- The reconciliation of heaven and earth.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Identity (Psychology) -- Religious aspects -- Christianity; Self (Philosophy); Self; RELIGION / Christian Theology / Anthropology; Electronic books